Self-presentation strategies of Instagram female users: A postmodern feminist analysis - Akritidou, Aikaterina; Megaris, Stavros; Georgaca, Eugenie (Psychology: the Journal of the Hellenic Psychological Society, 2024)
Instagram is a popular contemporary means of self-presentation and self-disclosure for women, with both positive and negative effects on their self-identification. This study explores how young female Instagram users’ identity is constructed through the analysis of their self-presentation management strategies. 16 semi-structured interviews with active female Instagram users were conducted using the visual method of photo-elicitation and analyzed using thematic analysis. Drawing upon postmodern feminist theories, four main themes emerged: the woman in Instagram, posting photos as a means of self-presentation, as a means of interaction with others, and as a means of constructing female identity. The participants seem to value the experience of their digital self-presentation as an enjoyable process that they willingly engage in while projecting an image permeated by the social imperatives for femininity; this is in line with cultural practices of post-feminism.